The circularity of the business model and the performance of bioeconomy firms: An interactionist business-environment model - Alberto Alcalde-Calonge; Pablo Ruiz-Palomino; Francisco José Sáez-Martínez (Cogent Business & Management, 2022)
Drawing on the Sustainable Development Goals of the UN 2030 Agenda, the implementation of circular economy business models (CEBMs) is key for reducing the impacts of business production modes on the environment and is especially suited to, and necessary in, the bioeconomy sector. The purpose of this literature review article is to analyse how firms in this sector can achieve a higher level of circularity in their business models, and how this circularity is positive for the triple bottom line. Building on the theories of social capital, new institutionalism and the triple bottom line (TBL), this article proposes a model to better understand how forest bioeconomy firms can develop high-circularity business models that lead them to excel on the TBL. This study combines internal aspects of the business (e.g., social capital, dynamic capabilities, entrepreneurial orientation) with situational variables (social/cultural, regulatory, technological, economic/financial drivers) to explain the level of circularity of business models in bioeconomy firms, as a prior step to enhancing their TBL. The interactionist model proposed is new to the literature and improves our understanding of how the level of circularity of a BM can be enhanced. The propositions derived will help to structure and design future research.
Keywords: 650; business/environment factors; circular economy; circularity level; entrepreneurial orientation; social capital